Community Partnership for Ecotourism Based on an Environmental Education Program for Sustainable Development in Sierra de Huautla, México - Alonso, Gabriela; Dhakal, Subas P. (Utopía y Praxis Latinoamericana, 1970)
The need for effective environmental education programs in the Latin American region has been made evident by deteriorating environmental conditions. The potential of ecotourism to contribute to environmental education programs with the community”™s partnership has increasingly been acknowledged in the recent years. This article illustrates the partnership between the community of Sierra de Huautla in south-central México and Morelos State University and the community in utilizing the ecotourism opportunity as a means for achieving environmental education objectives. The partnership between an academic institution and the local community has yielded the development of an environmental education curriculum as well as teaching materials based on local knowledge that are now being incorporated into formal education curricula. This article recommends that a framework and indicators be developed to evaluate the outcomes so that the curriculum can be tested, revised and replicated in other communities of the region Â